Study on Novel Yaw Error Strategy for Wind Turbines Based on a Multi-Body Dynamics Method - Wang, Yazhou; Cai, Xin; Xu, Bofeng; Li, Zhen (Frontiers in Energy Research, 2021)
At present, using structural dynamics models is the most commonly used and effective method to simulate the dynamic characteristics of large wind turbine. This paper used the multi-body dynamics method to construct the precise multi-flexible body dynamics model of a wind turbine coupled with aerodynamics/structure/control. The model can realize multi-disciplinary co-simulation interactions, and the accuracy was verified by comparing the numerical simulation data with the measured data. The allowable yaw error of a wind turbine is typically simplified to two or three fixed values according to the wind speed range, which cannot often adapt to the high and unsteady change characteristics of wind speed and direction under special conditions. In this paper, an accurate calculation method of allowable yaw error threshold based on measured wind speed and the corresponding optimization strategy of large yaw error are proposed, which not only avoid unnecessary shutdown and improve the availability, but also reduce the load of yaw bearing and improve the safety.